2009
DOI: 10.1002/pssc.200880932
|View full text |Cite
|
Sign up to set email alerts
|

DAP emission band in a carbon doped (1‐101)GaN grown on (001)Si substrate

Abstract: Optical spectra of a C‐doped (1‐101) GaN are investigated via time resolved photoluminescence spectroscopy. Samples with different C‐doping levels were prepared by metalorganic vapour phase epitaxy using C2H2 as the doping precursor. A carbon related emission peak is identified at 375 nm which shows typical behaviours for a donor‐acceptor‐pair emission band. The acceptor level is estimated to be 190 meV which is at 43 meV shallower than that in an Mg doped GaN. (© 2009 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, we might conclude that the 361 nm emission band is observable only in the GaN grown on the (1-1 0 1) GaN surface and is broader than the defect-related peak at 363 nm. Similar doping experiments were attempted in a (0 0 0 1) GaN as well as in a semipolar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN on silicon substrates. In both cases, we had DBE peak at 358 nm followed by a subsidiary peak at around 366 nm (3.388 eV).…”
Section: Sample Properties and Optical Spectramentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we might conclude that the 361 nm emission band is observable only in the GaN grown on the (1-1 0 1) GaN surface and is broader than the defect-related peak at 363 nm. Similar doping experiments were attempted in a (0 0 0 1) GaN as well as in a semipolar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN on silicon substrates. In both cases, we had DBE peak at 358 nm followed by a subsidiary peak at around 366 nm (3.388 eV).…”
Section: Sample Properties and Optical Spectramentioning
confidence: 84%
“…In addition to the 361 nm emission band, Honda et al [17] found a DAP emission band at 375 nm (3.306 eV). By the blueshift as a function of the excitation intensity and the redshift in time resolved photoluminescence (TRPL) analyses, they determined the acceptor level of 86 meV in the order of magnitude agreement with the above-mentioned values.…”
Section: Sample Properties and Optical Spectramentioning
confidence: 98%
“…Theoretical estimations so far suggest that the acceptor level due to carbon will be 150 ~ 200meV, larger than the values observed in the present studies. Honda et al [19] investigated the time resolved (TR-) PL spectra at low temperatures and found a new peak at 375nm. By analyzing the spectra as a function of excitation intensity and/or delay time, they concluded that the emission band at 375nm is due to donor acceptor pair (DAP) emission.…”
Section: Incorporation Of Carbonmentioning
confidence: 98%
“…Therefore the wafer size of the semipolar material is limited to ten millimeters. We have attempted HVPE growth of semioplar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and non-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) GaN on Si substrate [21,22]. In the HVPE growth of GaN on Si, the reaction of GaN with Si has been the issue [23].…”
Section: Summary and Future Prospectsmentioning
confidence: 99%